Factors that Influence Men and Women Participation in Microcredit Programme in Lagos State, Nigeria: A Case Study of Cowries Microfinance Bank (CMD) - Olateju, Adijat Olubukola (European Scientific Journal, ESJ, 2018)
Financial inclusion is paramount for economic growth, economic development, job creation, and poverty reduction. Evidence has shown that to ensure financial inclusion policy measures and developmental programmes need to be country specific and should be based on individual country’s gender gap. Given this, this study examined the factors that determine men and women entrepreneursâ€™ access to microcredit programme in Lagos State, Nigeria. A total of 359 female micro-entrepreneurs and 191 male microentrepreneurs were selected through a simple random sampling method among the customers of Cowries Microfinance Bank (CMB). Data were analysed with descriptive statistics and logistic regression. The results of the logistic regression show that only four of the variables used in measuring the determinants of participation in the credit programme were significant for the male entrepreneurs while for the female entrepreneurs, almost all the variables were significant except the age variable of the respondents. It is therefore, recommended that policymakers, microfinance banks, NGOs are advised to consider the age, number of years of education, political involvement and experience of the male entrepreneurs when granting loan facility to the male. However, for the female entrepreneurs, policymakers should take cognizance of the marital status, years of education, experience acquired in the business, size of the household, political membership, and level of income when providing credit facilities to the female entrepreneurs. Consequently, this will help to ensure that loan facility is given to the right person so that the gender gap regarding credit accessibility are closed, thereby leading to economic growth and sustainable economic development.